Update on pulmonary arterial hypertension research: proceedings from a meeting of experts. (1st February 2018) - McLaughlin, Vallerie; Bacchetta, Matthew; Badesch, David; Benza, Raymond; Burger, Charles; Chin, Kelly; Frantz, Robert; Frost, Adaani; Hemnes, Anna; Kim, Nick H.; Rosenzweig, Erika B.; Rubin, Lewis
Abstract: Background: While pulmonary arterial hypertension (PAH) remains a progressive, symptomatic condition characterized by increased pulmonary vascular resistance, ultimately leading to right heart failure, great strides have been made in its understanding and treatment over the past two decades. Review: Continued research in pre-clinical, clinical, and health economic areas of research, in addition to registry analyses and technology advances, is critical for understanding the pathophysiology of the disease and devising the best ways to monitor and manage patients. On December 3, 2016, the latest pre-clinical, clinical, health economic outcome, and registry data on PAH was presented in a symposium sponsored by Actelion. This paper reviews the published research and insight into upcoming research that was presented at this interactive meeting.